The self-esteem piauiense, the political uses and the repercussions on memory (Tempo e Argumento, 2021)
This text discusses how the means of representation produced by and about the government of Alberto Silva, in his first administration as governor of the state of Piauí (1971-1975), contributed to spread the belief about this government being the main responsible for the construction of piauiense self-esteem, and therefore for the formation of piauiense identity. The text aims to discuss how these discourses resonated in the memory and history of the local community to the point of radiating even among the political opponents of the said administrator. We argue that this project of construction of an optimistic ideal was not restricted to Piauí, and that it did not occur in isolation and unusual, as a result of the decision of one man, and that it was articulated to the historical configuration in force in the country. To this end, we use the concepts of identity - from the contributions made by Stuart Hall and Zygmunt Bauman; memory - from the studies carried out by Paul Ricœur and Michel de Certeau - and representation, in the discussions of Roger Chartier. Based on document criticism and on the Oral History methodology, we analyzed the official documents, journalistic articles published in national printed media and in local television, which approached this theme during and after the end of his government, as well as reports from the governor himself, from his allies, and from his political opponents, in order to understand how these discursive constructions influenced the history and the memory of Piauí.Keywords: History; policy; identity; memory.